Pakistani and Bangladeshi heritage mothers’ provision of primary education to their children in England during COVID-19: recommendations for involving mothers in policy decision-making processes [version 2; peer review: 2 approved] - Aliya Khalid; Kate Spencer-Bennett; Lavinia Kamphausen (Routledge Open Research)
During COVID-19, children have suffered learning losses across the world which will likely be carried forward to the future. In England, research and various reports were conducted to understand the extent of learning loss so policy could be improved for a more equitable educational provision. Two key areas were highlighted because of these investigations. Firstly, children in marginalised communities suffered the greatest share of educational disadvantages during COVID-19. Secondly, there is a scarcity of knowledge around the processes surrounding educational environments of learners. This study focused on mothers as partners and facilitators of education especially during COVID-19. Interviews were conducted with eight mothers in England with Pakistani and Bangladeshi heritage exploring their experiences of educating their primary school-aged children during COVID-19. The perspectives of mothers shared with the researchers were analysed by focusing on the physical spaces and the psychological aspects that were experienced since the inception of the pandemic. The findings reveal that mothers were working at multiple fronts to help their children transition smoothly to a new way of learning and living by making a series of contributions. Firstly, mothers adapted the physical spaces so they would suit their children’s learning needs. Secondly, they structured time to bring some normalcy to the disrupted patterns of living. Thirdly, they drew on social relations to compensate for the socio-emotional gaps that lockdown situations were creating for children. Lastly, they redefined the meaning of education and its advantages and integrated the social and cultural with the formal aspect of education. The findings suggest that policy reform to rehabilitate an equitable education system will need to draw on these rich perspectives. It will be essential for policy discussions in the future to include the lived experiences of mothers in providing timely and tailored educational support to their children.